Respuesta :
Answer: y=-3x-1
Explanation: Sub the coordinates into y=mx+c to find c
-4=-3x1+c
-4=-3+c
c=-1
Then just re write it in y=mx+c to get y=-3x-1
Explanation: Sub the coordinates into y=mx+c to find c
-4=-3x1+c
-4=-3+c
c=-1
Then just re write it in y=mx+c to get y=-3x-1
[tex](\stackrel{x_1}{1}~,~\stackrel{y_1}{-4})\qquad \qquad \stackrel{slope}{m}\implies -3 \\\\\\ \begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-\stackrel{y_1}{(-4)}=\stackrel{m}{-3}(x-\stackrel{x_1}{1}) \\\\\\ y+4=-3x+3\implies y=-3x-1[/tex]